Ответ:
Пошаговое объяснение:
1) |х| + 3 = 5
|х| = 2
x = ±2
2) |y| - 2 = 1
|y| = 3
y = ±3
3) x + 3 = 0 при х + 3 >= 0
x = -3
-(x + 3) = 0 при х + 3 < 0
-x - 3 = 0
4) x - 5 = 0 при х - 5 >= 0
x = 5
-(x - 5) = 0 при х - 5 < 0
-x + 5 = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) |х| + 3 = 5
|х| = 2
x = ±2
2) |y| - 2 = 1
|y| = 3
y = ±3
3) x + 3 = 0 при х + 3 >= 0
x = -3
-(x + 3) = 0 при х + 3 < 0
-x - 3 = 0
x = -3
4) x - 5 = 0 при х - 5 >= 0
x = 5
-(x - 5) = 0 при х - 5 < 0
-x + 5 = 0
x = 5